ANALISIS PENGARUH RASIO SERAT RAMI DAN HIDROKSIAPATIT TERHADAP KEKUATAN MEKANIK KOMPOSIT BERMATRIKS UHMWPE DENGAN METODE HOT PRESS - Fathoni, Achmad Luthfian; Salahudin, Xander; Hastuti, Sri (ELEMEN : JURNAL TEKNIK MESIN, 2025)
Composite is a material made from two or more combined substances that are bound together. Typically, biomaterials are made of metals. However, metals have a high elastic modulus, which leads to stress shielding, and they are expensive because metals are non-renewable materials. This study aims to analyze the mechanical strength of composites made from ramie fiber, hydroxyapatite, and UHMWPE as a potential non-metallic biomaterial, with variations in composition of 13%: 0%: 87%, 6.5%: 6.5%: 87%, and 0%: 13%: 87%. The composites were manufactured using a hot press at a temperature of 190°C, pressure of 100 bar, and a holding time of 15 minutes. The test results showed the composite containing 13% ramie fiber having the highest impact toughness and tensile strength values of 0.055 J/mm² and 10.75Mpa.